2010
DOI: 10.1002/chem.201001233
|View full text |Cite
|
Sign up to set email alerts
|

Ketone–Alcohol Hydrogen‐Transfer Equilibria: Is the Biooxidation of Halohydrins Blocked?

Abstract: Abstract:In order to ensure the quasiirreversibility of the oxidation of alcohols coupled with the reduction of ketones in a hydrogen transfer (HT) fashion, stoichiometric amounts of α-halo carbonyl compounds as hydrogen acceptors have been employed. The reason why these substrates lead to quasi-quantitative conversions has been tacitly attributed to both thermodynamic and kinetic effects. In order to provide a clear rationale for this behavior, we study here the redox equilibrium of a selected series of keton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 51 publications
5
39
0
Order By: Relevance
“…Because these ILs did not act as an appropriate hydrogen donor/acceptor with ADHs due to possible destabilizing interactions with the enzyme, a hydrogen transfer reaction with the aluminium tert-butoxide catalyst Al(O t Bu) 3 was envisaged (Scheme 4). Previous results with this catalyst have shown that when using 2-propanol for the reduction of ketones (Scheme 4a), or acetone for the oxidation of secondary alcohols, similar conversions to that observed with LBADH and ADH-A as biocatalysts were achieved [47]. Hence, whereas the reduction of 6a to 6b using 2-propanol as co-substrate with the aluminium catalyst afforded 86% of conversion, in the same reaction conditions with IL 1 only 7% of conversion was achieved (Scheme 4b).…”
Section: Adh-catalysed Biooxidations With Ilsupporting
confidence: 60%
“…Because these ILs did not act as an appropriate hydrogen donor/acceptor with ADHs due to possible destabilizing interactions with the enzyme, a hydrogen transfer reaction with the aluminium tert-butoxide catalyst Al(O t Bu) 3 was envisaged (Scheme 4). Previous results with this catalyst have shown that when using 2-propanol for the reduction of ketones (Scheme 4a), or acetone for the oxidation of secondary alcohols, similar conversions to that observed with LBADH and ADH-A as biocatalysts were achieved [47]. Hence, whereas the reduction of 6a to 6b using 2-propanol as co-substrate with the aluminium catalyst afforded 86% of conversion, in the same reaction conditions with IL 1 only 7% of conversion was achieved (Scheme 4b).…”
Section: Adh-catalysed Biooxidations With Ilsupporting
confidence: 60%
“…Thus, we have observed that carbonyl groups presenting an electron-withdrawing moiety at α-position can be quasi-irreversibly reduced by ADHs. [23,27,28] This effect has also been observed in the case of bioreductions of 1,2-and 1,3-diketones, probably due to the fact that an intramolecular H-bond is formed between the formed alcohol moiety and the remaining carbonyl group, hampering their oxidation reaction. [29] With this in mind, we envisaged that bioreductions of these β-ketoester derivatives could be highly favoured due to the formation of an intramolecular H-bond affording a stabilised 6-member ring (Figure 2), and therefore a small excess of 2-propanol could be used to achieve quantitative conversions of the corresponding β-hydroxyesters.…”
Section: Dkrs Under 'Quasi-irreversible' Conditionsmentioning
confidence: 89%
“…Since these transformations mainly rely on the thermodynamic equilibrium between the redox pairs of substrate and cosubstrate, [27] depending on the chemical structure of compounds reduced/oxidised, the reaction equilibrium will be easily (or not) displaced into the final products. Thus, we have observed that carbonyl groups presenting an electron-withdrawing moiety at α-position can be quasi-irreversibly reduced by ADHs.…”
Section: Dkrs Under 'Quasi-irreversible' Conditionsmentioning
confidence: 99%
“…Due to the high difficulty to oxidize halohydrins, 14 it was envisioned the employment of a potent oxidant such as Jones' reagent. Thus, following a typical procedure, 15 using a mixture of acetone/water (40:1 v v -1 ) at 0ºC afforded, by TLC, the desired compound, but when the solvent was evaporated under vacuum to obtain 10, the high volatility of this ketone avoided its adequate isolation.…”
Section: Scheme 3 Fluorination Conditions Over Chlorohydrinmentioning
confidence: 99%